PENGARUH KONSUMSI OBAT OLEH IBU HAMIL TERHADAP JANIN YANG DIKANDUNG - Winarti, Lina; Wisudyaningsih, Budipratiwi (FKM - UNEJ, 2007)
Pregnant woman is possible to expose with disease which need to cure by using drugs. Sometimes a woman suffer from chronic disease should take some medicine, even in pregnant condition. Risk of harm effect happened on consuming drug at pregnant condition depend on type & when the drug given. In first two week, growth of fetus embryo is known by the most critical effect of teratogenic defect because of drug administration. Most critical period of growth of embryo started about 17 day of post impregnation when system organ expanding. It is last until 60 -70 days. Administration of certain drugs on that period can give teratogenic effect. Administration of drug on pregnant woman should be carried with extra attention, because of the possible risk that can occur during a period of pregnancy. If pregnant woman canât avoid not taking drug therapy, she has to counsel with physician to decide what kind of drug she should take. On the other side, before giving drug therapy physician has to consider about drug safety, dosage, usage duration, type of drug & wayÂ the drug should given.